Dietary reference values for chloride. (4th September 2019) - ,; Turck, Dominique; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen‐Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Pelaez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) has derived dietary reference values (DRVs) for chloride. There are no appropriate biomarkers of chloride status, no balance studies and no adequate evidence on the relationship between chloride intake and health outcomes that can be used to set DRVs for chloride. There is a close relationship between sodium and chloride balances in the body. Sodium chloride is the main source of both electrolytes in European diets and similar urinary excretion levels of sodium and chloride (on a molar basis) are typically observed in Western populations. Hence, the Panel considered that reference values for chloride can be set at values equimolar to the reference values for sodium for all population groups, and are as follows: 1.7 g/day for children aged 1–3 years, 2.0 g/day for children aged 4–6 years, 2.6 g/day for children aged 7–10 years, 3.1 g/day for children aged 11–17 years and 3.1 g/day for adults including pregnant and lactating women. Consistent with the reference values for sodium, these levels of chloride intake are considered to be safe and adequate for the general EU population, under the consideration that the main dietary source of chloride intake is sodium chloride. For infants aged 7–11 months, an adequate intake of 0.3 g/day is set. Abstract : This publication is linked to the following EFSA Supporting Publications articles: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1679/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.e15121/full This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5778/full